Determinants of Purchase Intention of Skincare Products, Brand Image as Moderation On The Tiktok Platform - Nadia Agustini; Elistia Elistia (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
With the rapid development of Internet technology, many companies are now using the Internet as a major platform in their marketing strategy of skincare products, mainly through social media. The research aims to explore the factors that influence the intention of buying skincare products on the TikTok platform by considering the role of brand image as a moderation variable. The research method uses descriptive causality with a quantitative approach, and uses purposive sampling techniques. Primary data obtained from 267 respondents active TikTok users who were interested in skincare products and collected through online questionnaires. Data analysis is done using Structural Equation Modelling-Partial Least Square (SEM-PLS). Research findings show that social media marketing activities, online customer reviews, influencer endorsement, brand image can improve purchase intention, while price consciousness does not affect the purchase intent of skincare products on Tiktok platform. Implications, skincare manufacturers and marketers should pay attention to branding strategies on TikTok's platform to boost purchasing intentions. Further research is suggested to explore other factors that can influence the intention of buying skincare products in the digital age.